RELIGIÃO E MST: ESTUDO DOS BATISTAS DA CONGREGAÇÃO MONTE SIÃO NO ASSENTAMENTO ANTONIO CONSELHEIRO II NA REGIÃO DO PONTAL DO PARANAPANEMA - Dinizz Júnior, José Américo (2007)
The insertion of an evangelical church in a rural settlement of the Rural Workers Without Land Movement (MST) is the objective of our case study within this present paper. The thesis researches and analyzes the entrance of Baptist evangelicals in the Antonio Conselheiro II settlement located in the region of Pontal do Paranapanema in the state of São Paulo, as well as the subsequent planting there of the Monte Sião Baptist Congregation. Beginning from a theoretical and empirical perspective, the objective is focused on analyzing the life experience of the Baptist settlers within the settlement, seeking to describe the forms, both conceptual and practical, in which these people live out their faith, customs and beliefs, dreams and ideals, always seeking to tease out the relations that best facilitate an evaluation of the forms as the settlers themselves understand and communicate their faith while participants of the MST. From the critical appreciation of the stories obtained in the interviews and the information from the questionnaire, both applied to the subjects of the study, develops a account that uncovers the faces of a relational identity that mixes ideology and faith, being Baptist evangelical and a MST settler, as well as an internalized proposition of a non-violent methodology in the public manifestations of the Without Land Movement.(AU)